An open-label randomized controlled trial of the effect of lopinavir/ritonavir, lopinavir/ritonavir plus IFN-β-1a and hydroxychloroquine in hospitalized patients with COVID-19. (December 2021) - Ader, Florence; Peiffer-Smadja, Nathan; Poissy, Julien; Bouscambert-Duchamp, Maude; Belhadi, Drifa; Diallo, Alpha; Delmas, Christelle; Saillard, Juliette; Dechanet, Aline; Mercier, Noémie; Dupont, Axelle; Alfaiate, Toni; et al.
Abstract: Objectives: We evaluated the clinical, virological and safety outcomes of lopinavir/ritonavir, lopinavir/ritonavir–interferon (IFN)-β-1a, hydroxychloroquine or remdesivir in comparison to standard of care (control) in coronavirus 2019 disease (COVID-19) inpatients requiring oxygen and/or ventilatory support. Methods: We conducted a phase III multicentre, open-label, randomized 1:1:1:1:1, adaptive, controlled trial (DisCoVeRy), an add-on to the Solidarity trial (NCT04315948, EudraCT2020-000936-23). The primary outcome was the clinical status at day 15, measured by the WHO seven-point ordinal scale. Secondary outcomes included quantification of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in respiratory specimens and pharmacokinetic and safety analyses. We report the results for the lopinavir/ritonavir-containing arms and for the hydroxychloroquine arm, trials of which were stopped prematurely. Results: The intention-to-treat population included 583 participants—lopinavir/ritonavir ( n = 145), lopinavir/ritonavir–IFN–β-1a ( n = 145), hydroxychloroquine ( n = 145), control ( n = 148)—among whom 418 (71.7%) were male, the median age was 63 years (IQR 54–71), and 211 (36.2%) had a severe disease. The day-15 clinical status was not improved with the investigational treatments: lopinavir/ritonavir versus control, adjusted odds ratio (aOR) 0.83, (95% confidence interval (CI) 0.55–1.26, p 0.39), lopinavir/ritonavir–IFN–β-1a versus control, aOR 0.69 (95%CI 0.45–1.04, p 0.08), and hydroxychloroquine versus control, aOR 0.93 (95%CI 0.62–1.41, p 0.75). No significant effect of investigational treatment was observed on SARS-CoV-2 clearance. Trough plasma concentrations of lopinavir and ritonavir were higher than those expected, while those of hydroxychloroquine were those expected with the dosing regimen. The occurrence of serious adverse events was significantly higher in participants allocated to the lopinavir/ritonavir-containing arms. Conclusion: In adults hospitalized for COVID-19, lopinavir/ritonavir, lopinavir/ritonavir–IFN–β-1a and hydroxychloroquine improved neither the clinical status at day 15 nor SARS-CoV-2 clearance in respiratory tract specimens.